Research methods for business students / Mark N.K. Saunders, Philip Lewis, Adrian Thornhill. - Saunders, M. N. K.; Lewis, Philip, 1945-; Thornhill, Adrian (Pearson, 2023)
Support your students' research project with robust and pragmatic guidance on the entire process. This book introduces a range of features, including a glossary of terms, case studies and articles, and self-study prompts that will encourage your students to apply what they have learned to their own research project.